Ideology and foreign policy in early modern Europe (1650-1750) - Onnekink, David; Rommelse, Gijs, 1977- (Politics and culture in Europe, 1650-1750., 2011)
By engaging with, and building upon recent theoretical developments, this collection sheds new light on international relations in the century between 1650 and 1750. Integrating cultural history with high politics and foreign policy, it also engages directly with themes discussed by political scientists and international relations theorists to argue that, this was far from being a 'de-ideologized' period. Instead it offers a fresh and genuinely interdisciplinary perspective to this complex and fundamental period in Europe's development, and one which puts ideology at its core.